THE INVERTED DISTORTED PARABOLA-LIKE SHAPE OF THE BIAS-DEPENDENT ELECTRIC FIELD AT AN ELECTRON-INJECTING METAL/ORGANIC INTERFACE DEDUCED USING THE CURRENT-VOLTAGE METHOD - Koželj, Matjaž; Cvikl, Bruno (Journal of Energy Technology, 2024)
Using the recently derived expression for the traditional Mott-Gurney charge-drift model extended by the non-zero electric field at the charge-injecting interface Eint, the published dependence of the current density on the applied electric field j–Ea for two good-ohmic-contact, electron-only, metal/organic structures is analysed. It is argued that the Mott-Gurney law with the well-known empirical exponential bias-dependent mobility included, in spite of a very good fit to the j–Ea measurements, represents an unsatisfactory method for data analyses. It is shown that the internal electric field at the electron-injecting interface is strongly bias dependent, and in such a way is coupled to the electron current within the organic bulk. The bias dependence of the interfacial field resembles an inverted, distorted, parabola-like-shaped curve, the maximum of which is organic-material dependent. Beyond the maximum, which occurs at high values of the externally applied electric field Ea, the interfacial electric field Eint exhibits a rapid decrease towards zero, and only at this limit can the traditional Mott-Gurney law be applied. In contrast to the present notion, it is found that the (large) electron effective mobility for the two samples investigated does not change with the bias, but it is the total effective mobility (its product with the specific non-linear algebraic function of Ea) that is bias dependent. The effective mobility may be uniquely determined, providing the applied electricfield spans a sufficiently wide Ea interval. It is argued that an appropriate width of this interval may be tested by the judicious application of the derived expression in the limit Eint ® 0. The Alq3 bias- dependent interfacial electric field at the electron injecting cathode/organic junction results in a non-linear response of the corresponding free electron density, nfree(L=200 nm), at this site. The possibility for an investigation of the electric field at the charge-injecting metal/organic interface using the j–V method is therefore outlined.
Keywords: Metal-organic interface; Electric field; Bias-dependent interfacial field; Current density modelling; Effective electron mobility; Organic semiconductors